Dancing Through Mythological Threads: Unraveling the Symbolism of Chechen Dance - Maysa Bakeer (Sakarya İletişim)
The incorporation of mythology into Chechen cultural practices and rituals, particularly in the realm of traditional dances, holds significant importance. By delving into the realms of myth and storytelling, Chechen dance gains a heightened sense of depth and appreciation, forging connections between the audience and the profound layers of symbolism, historical context, and spiritual essence embedded within the art form. This study aims to shed light on these cultural connections by exploring the similarities between Chechen culture and Greek mythology, with a particular focus on the iconic figures of Artemis and Apollo. These mythical beings bear unique characteristics that resonate with the essence of Chechen dance, particularly in their representation of celestial bodies such as the sun and moon, as well as their associations with various animal motifs. Moreover, the emblem of İchkria, proudly displayed on the Chechen flag, serves as a symbolic thread that ties together this captivating exploration. Through this inquiry, a deeper understanding of the intricate interplay between mythology, dance, and cultural identity in Chechen tradition is sought.